A genetic ant colony algorithm for routing in CPS heterogeneous network. (19th December 2013) - Gao, Zhijun; Ren, Jingya; Wang, Changtao; Huang, Kuan; Wang, Hongyu; Liu, Ying
Cyber–physical system (CPS) is the developing trend of the network in the next generation. According to the characteristics and requirements of CPS, in this paper, we propose a CPS network architecture which mainly consists of four layers, physical layer, network layer, transport layer and application layer. Because of the heterogeneity of CPS, the guarantee of the quality of service (QoS) is the key challenge for the network. The genetic algorithm and the ant colony algorithm are both effective methods for the routing issues, but they both have obvious disadvantages. In this paper, we combine the two algorithms for efficient routing in CPS. Simulation results show the proposed algorithm performs better.